Posterior Reversible Encephalopathy Syndrome with Blood Transfusion? - Kumar, Mukesh; Pooran Mal; Sunil; Aqsa (LIAQUAT MEDICAL RESEARCH JOURNAL, 2022)
Posterior Reverse Encephalopathy Syndrome (PRES) is a clinico-neuro-radiologic entity with various neurological manifestations, including headaches, vision problems, and altered mental status. Oedema has been observed in a generally symmetrical fashion in MRI studies, most often in the subcortical white matter and rarely in the cortex of the occipital and parietal lobes. When properly treated, this condition is usually reversible; however, failure to make a timely diagnosis may result in cerebral infarction and even death. This case report presents a 30-year-old woman with a history of postpartum bleeding and anuria, later diagnosed with PRES syndrome. This rare case is reported here for information of neurology clinicians to keep the features in mind if any such case comes up in future.